Advances in Understanding Recurrent Pulmonary Infections Following Foreign Body Aspiration: A Narrative Review - Tang Q; Chen X; Ran K; Yang X; Yuan T; Li J; Zheng J; Xu C; Li H; Zhao Y; Wang J (Journal of Asthma and Allergy, 2025)
Qian Tang,1,* Xing Chen,2,3,* Kunjie Ran,4 Xueqin Yang,1 Ting Yuan,1 Juanjuan Li,1 Juan Zheng,1 Chen Xu,1 Heping Li,1 Yang Zhao,1 Jingsong Wang1 1Department of Pharmacy, Guangyuan Central Hospital, Guangyuan, Sichuan, People’s Republic of China; 2School of Stomatology, North Sichuan Medical College, Nanchong, Sichuan, People’s Republic of China; 3Department of Stomatology, Guangyuan Central Hospital, Guangyuan, Sichuan, People’s Republic of China; 4Department of Pharmacy, The First People’s Hospital of Guangyuan, Guangyuan, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingsong Wang, Department of Pharmacy, Guangyuan Central Hospital, Guangyuan, Sichuan, People’s Republic of China, Email wjs5515@163.com Yang Zhao, Department of Pharmacy, Guangyuan Central Hospital, Guangyuan, Sichuan, People’s Republic of China, Email 591914757@qq.comAbstract: Recurrent pulmonary infections (RPIs) represent a common yet clinically complex entity, primarily triggered by aspiration or the presence of foreign bodies. They are notoriously insidious and challenging to detect clinically. These infections typically involve the invasion of bacteria, viruses, or fungi, leading to inflammation and damage of lung tissue. The development of RPIs may also arise from the interplay of multiple factors. Due to their inherent complexity and association with poor prognosis, RPIs constitute a significant cause of mortality stemming from pulmonary infections. Understanding the risk factors associated with RPIs secondary to foreign body aspiration is crucial for effective clinical management. This narrative review synthesizes current knowledge on the pathogenesis, diagnosis, management, and prevention of RPIs caused by foreign body aspiration. We emphasize the heightened vulnerability of pediatric and elderly populations. The review delineates characteristic clinical presentations and outlines appropriate diagnostic modalities. Furthermore, it provides perspectives on antimicrobial therapy and the critical importance of foreign body removal. The synthesis aims to inform future research directions, preventive strategies, and therapeutic approaches, ultimately seeking to improve patient outcomes and mitigate the risk of recurrent infections.Keywords: foreign body aspiration, pulmonary infection, recurrence, diagnosis and treatment, prevention